URGENSI BERPIKIR KRITIS DALAM MEMBENTUK KEBIJAKSANAAN MEMBACA INFORMASI DI ERA DIGITAL UNTUK MENGATASI HOAKS DAN DISINFORMASI - Intan Pratiwi; Purwanti, Purwanti (Cahaya Ilmu Bangsa, 2025)
The development of technology and increasingly widespread access to information in the digital era have had a significant impact on the way people obtain and utilize information. However, this convenience comes with major challenges in the form of the rise of hoaxes and disinformation that can influence public opinion, decision-making, and social stability. In this context, critical thinking becomes a very urgent skill to develop. Critical thinking allows individuals to analyze, disseminate, and validate information systematically so that they are able to distinguish between facts, opinions, and information that is spun or manipulative. Moreover, critical thinking also plays an important role in shaping the wisdom of reading information, namely the ability to measure wisely, skeptically, and align in receiving information. This article explores the urgency of critical thinking as the main tool in dealing with the threat of disinformation in the digital era. This approach not only aims to protect individuals from the negative impacts of hoaxes, but also supports the creation of a healthy and responsible digital literacy culture. This study provides the integration of critical thinking in the education curriculum, community training, and public policy as a strategic step to overcome the challenges of disinformation that continues to grow. Thus, it is hoped that society will be able to adapt in dealing with the complexity of digital information wisely and responsibly.